LO SPAZIO DELL'ARTE DELLA PAROLA NELLA RIFLESSIONE ESTETICA DI WŁADYSŁAW STRÓŻEWSKI - cl, redakcja (Colloquia Litteraria, 2020)
The Role of the Art of the Word in Władysław Stróżewski's Aesthetic Reflection The article explains how the philosophical analyses of Cyprian Norwid's, Bolesław Leśmian's, and other poets' writing play a critical role in Władysław Stróżewski's aesthetics. His decision to look at the basic themes in aesthetic (and anthropology) from the perspective of the art of the word let to a novel elaboration of the knowledge of beauty and in an original manner directed it towards further axiological reflection.